The Survival of Faith in Solzhenitsyn’s One Day in the Life of Ivan Denisovich and “Matryona’s House” - Wawan Eko Yulianto (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
Faith is a vital element in the works of Nobel laureate Alexander Solzhenitsyn, a Russian writer who experienced the notorious Gulag and difficultly in a strongly atheistic country. However, faith is never a simplistic topic for Solzhenitsyn, especially writing in a time when religion was officially shoved aside from the public discourse. In the light of a set of views on religion inferred from Terry Eagleton’s essay, this paper aims to explain the anomalous religiosity as seen in the narrators of Solzhenitsyn’s novel One Day in the Life of Ivan Denisovich and short story “Matryona’s House.” According to the Eagleton’s model, there are three stages of religiosity, namely, 1) omission of religion’s otherworldly and pure ritualistic elements, 2) acceptance of mentally-empowering potentials of religion, and 3) internalization of the humanistic values of religion. The analysis concludes with a notion that One Day in the Life of Ivan Denisovich and “Matryona’s House” represent an evolution of faith that has gone through a period of challenge. On a sidenote, the analysis also confirms the dialogic nature of Solzhenitsyn’s works, in which one topic is presented through contradictory voices.